The advances in diagnostic modalities of disorders of the long head of the biceps tendon – review - Gagat, Maciej; Zabrzyńska, Agnieszka; Zabrzyńska, Maria; Zielińska, Wioletta (Medical Studies/Studia Medyczne, 2021)
The broad spectrum of disorders of the long head of the biceps (LHBT) can be divided into 3 main categories: inflammatory reactions, degenerative conditions, and instability. More than 90% of patients with LHB tendinopathy have an additional shoulder pathology. Thus, a detailed radiological and histopathological evaluation is crucial for a complete and accurate diagnosis. The pathology of the LHBT starts from its ultrastructure with the alterations of both tenocytes and extracellular matrix. Furthermore, this is reflected in the light microscopy investigation, with marginal inflammatory response. The ultrasonography is useful in the detection of LHBT instability, hypoechogenic areas, increased tendon diameter, and dynamic examination of the tendon. A standard non-contrast magnetic resonance imaging (MRI) of the shoulder is a useful tool in the diagnostics of advance tendinopathy; however, it is essentially limited in the detection of partial tears. Based on current knowledge, ultrasound and MRI diagnostics modalities should be simultaneously used in the examination of LHBT disorders.